2017
DOI: 10.3389/feart.2017.00050
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 Degassing Path along Volcano-Tectonic Structures in the Pico-Faial-São Jorge Islands (Azores Archipelago, Portugal)

Abstract: The Azores archipelago is composed of nine volcanic islands located at the triple junction between the North American, Eurasian, and Nubian plates. Nowadays the volcanic activity in the archipelago is characterized by the presence of secondary manifestations of volcanism, such as hydrothermal fumaroles, thermal and cold CO 2 -rich springs as well as soil diffuse degassing areas, and low magnitude seismicity. Soil CO 2 degassing (concentration and flux) surveys have been performed at Pico, Faial, and São Jorge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 84 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Two statistical analysis procedures were applied to the CO 2 flux data, namely the graphical statistical approach (GSA) (e.g., [51]) and sequential Gaussian simulation (sGs) [56]. The GSA procedure is based on cumulative probability plots, leading to the identification of different populations in the geochemical data [57], which afterwards may be associated with diverse CO 2 sources, such as biogenic processes or volcanic-hydrothermal input (e.g., [24,35,36,51,56,58,59]).…”
Section: Co 2 Flux Data Processingmentioning
confidence: 99%
“…Two statistical analysis procedures were applied to the CO 2 flux data, namely the graphical statistical approach (GSA) (e.g., [51]) and sequential Gaussian simulation (sGs) [56]. The GSA procedure is based on cumulative probability plots, leading to the identification of different populations in the geochemical data [57], which afterwards may be associated with diverse CO 2 sources, such as biogenic processes or volcanic-hydrothermal input (e.g., [24,35,36,51,56,58,59]).…”
Section: Co 2 Flux Data Processingmentioning
confidence: 99%
“…In this context, the study of the spatial distribution of geochemical anomalies represents a valid additional tool to define and identify active buried structures and areas of active deformation as well. Actually, many studies showed as faults and fractures play a key role in the localization and evolution of geochemical anomalies at the surface [De Gregorio et al, 2002;Finizola et al, 2004;Finizola et al, 2006;Granieri et al, 2006;Werner and Cardellini 2006;Rowland and Simmons, 2012;Brothelande et al, 2014;Cellura et al, 2014;Viveiros et al, 2017]. This is because the migration of fluids through the crust occurs mainly through channels of high permeability generally represented by regional active faults or in sectors under active deformation [Sibson and Rowland, 2003;Fairley and Hinds, 2004;Dogan et al, 2007;Faulkner et al, 2010;Fossen and Rotevatn, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a great interest has been focused on studying of CO 2 Earth degassing. There are many targets for such research, such as the relationships between the CO 2 flux and the tectonic structures (Etiope et al, 1999;Jolie et al, 2015), the researches of volcanic degassing (Inguaggiato et al, 2012;Chen et al, 2019;Fischer and Aiuppa, 2020), and the quantification of deeply derived CO 2 discharging into the atmosphere (Lee et al, 2016;Viveiros et al, 2017;Jacome-Paz et al, 2020;Bekaert et al, 2021;Rahilly and Fischer, 2021).…”
mentioning
confidence: 99%